Studies on the inhibition of mild steel corrosion in hydrochloric acid solution by atenolol drug - G. Karthik; M. Sundaravadivelu (Egyptian Journal of Petroleum)
The inhibition performance of atenolol on mild steel in 1 M hydrochloric acid solution was studied by weight loss and electrochemical methods. The results show the inhibition efficiency was found to increase with increasing the concentration of the inhibitor from 50 to 300 ppm. The maximum inhibition efficiency 93.8% was observed in the presence of 300 ppm inhibitor (in case of potentiodynamic polarization). The inhibition action of atenolol was explained in terms of adsorption on the mild steel surface. The adsorption process follows Langmuir isotherm via physical adsorption. Electrochemical Impedance spectroscopic technique (EIS) exhibits one capacitive loop indicating that, the corrosion reaction is controlled by charge transfer process. Polarization measurements showed that the inhibitor is of a mixed type. The results obtained from the different methods are in good agreement. The surface morphologies of mild steel were examined by Fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscope (SEM). Further, the computational calculations are performed to find a relation between their electronic and structural properties.